Efektivitas Ekstrak Tomat (Solanum lycopersicum) dalam Meningkatkan Kualitas Spermatozoa Tikus Terpapar Asap Rokok - Imroatus Sholikhah; Yuyun Nailufar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Tomato (Solanum lycopersicum) extract is known to contain potent antioxidant compounds such as lycopene, vitamin C, and flavonoids that can protect reproductive cells from oxidative stress. This study aims to analyze the effectiveness of tomato extract in improving the quality of spermatozoa in white rats (Rattus norvegicus) exposed to cigarette smoke, which is a major source of free radicals. The research applied a literature review approach by identifying, selecting, and analyzing related studies published between 2013 and 2023 from the Google Scholar and Academia.edu databases. Ten eligible studies were included for synthesis. The results show that the administration of tomato extract at doses ranging from 20 to 60 mg/kgBW/day significantly increased sperm motility, morphology, and viability in rats exposed to cigarette smoke. The improvement was associated with the antioxidant effect of lycopene, which protects Leydig cells and maintains testosterone production. These findings suggest that tomato extract has significant potential as a natural antioxidant therapy to prevent oxidative damage and reproductive disorders caused by cigarette smoke exposure.